Islamic estate, retirement and waqf planning - Amir Bahari (IBFIM, 2014)
Estate planning is an area that actually covers both the Shariah and any country's civil laws, therefore it is important for Muslims to be well versed in such matters. This book provides an understanding on the intricacies and wider concepts of Islamic estates, and as such would be resourceful for estate planners, legal or financial practitioners, or anyone interested in the ideas of waqf and retirement within Islam. This book is based on the Malaysian experience of civil and religious law, however most concepts can be extrapolated to Muslims living in societies around the world.